2014
DOI: 10.1007/s12094-014-1167-9
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced expression of IMPDH2 promotes metastasis and advanced tumor progression in patients with prostate cancer

Abstract: These findings suggest for the first time that the enhanced expression of IMPDH2 may promote the tumor metastasis and the advanced tumor progression in patients with PCa.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
23
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(24 citation statements)
references
References 21 publications
1
23
0
Order By: Relevance
“…Increased expression of IMPDH2 is associated with progression of kidney and bladder cancer [35]. Promotion of metastasis and advanced tumor progression in patients with prostate cancer is also associated with increased IMPDH2 expression [36]. Likewise, gene expression of PDI ( PDIA3 and PDIA6 ) was shown to be a marker for aggressiveness in primary ductal breast cancer [37].…”
Section: Discussionmentioning
confidence: 99%
“…Increased expression of IMPDH2 is associated with progression of kidney and bladder cancer [35]. Promotion of metastasis and advanced tumor progression in patients with prostate cancer is also associated with increased IMPDH2 expression [36]. Likewise, gene expression of PDI ( PDIA3 and PDIA6 ) was shown to be a marker for aggressiveness in primary ductal breast cancer [37].…”
Section: Discussionmentioning
confidence: 99%
“…IMPDH2 is frequently overexpressed in different forms of leukemia [161], colorectal [162], prostate [18], bladder, and kidney cancers [163]. Moreover, there are several evidences that its expression is associated with highly invasive, metastatic cancers [18, 163] resistant to cisplatin and MTX [164, 165].…”
Section: Other Inhibitors Of Metabolismmentioning
confidence: 99%
“…Moreover, there are several evidences that its expression is associated with highly invasive, metastatic cancers [18, 163] resistant to cisplatin and MTX [164, 165]. …”
Section: Other Inhibitors Of Metabolismmentioning
confidence: 99%
See 1 more Smart Citation
“…suggested that IMPDH2 could be used as a promising candidate for the stratification of osteosarcoma patients into low- and high-risk groups 16 . Recently, the protein expression level of IMPDH2 was found to be significantly upregulated in prostate, kidney and bladder cancers and could be a potential biomarker for these diseases 2, 17 . However, to the best of our knowledge, the expression status of IMPDH2 and its clinical significance in NPC remain unknown.…”
Section: Introductionmentioning
confidence: 99%